Penerapan Teori Planned Behavior Dan Perceived Value Pada Online Purchase Behavior - Bangun, Cicilia Sriliasta; Suhara, Toni; Husin, Husin (Technomedia Journal, 2023)
This study aims to analyze the effects of perceived behavioral control, subjective norms, attitudes, and perceived value on purchase intentions and their effects on purchasing behavior. Extrinsic variables in this study are perceived behavioral control, subjective norms, attitudes, and perceived value. The endogenous survey variables are purchase intention and purchase behavior. The survey sample consisted of 113 respondents, consumers who shop at online shop X. The data collection method used a questionnaire. Methods of data analysis by SEM PLS. The study concluded that of the five hypotheses, only hypotheses 1 and 5 were significant.